Enhancing creativity in activity‐based offices: A critical incident study of knowledge workers. (18th October 2021) - Yekanialibeiglou, Sepideh; Demirkan, Halime; Denti, Leif
Abstract : This study investigated the effects of activity‐based offices (ABOs) on individual and group creativity. Adopting an interactionist perspective, we extended the theoretical framework of creative knowledge environments to find the link between ABOs and the concept of creative spaces. We employed the critical incident technique and collected data through interviews and participant observation methods for the case studies of three ABOs. The results show that privacy, noise level, and a distraction‐free environment were the main factors supporting employees' individual creativity, as were open spaces with zones for different levels of noise and private enclosed spaces. For group creativity, the significance of providing suitable equipment and furniture in ABOs was observed—collaborative and disengaged spaces were found to be the recurring spaces for group creativity. Additionally, employee preferences were noted as an important component to consider when looking at environmental features, types of spaces and types of creative activities in creativity‐enhancing ABOs.